Aphid effector Me10 interacts with tomato TFT7, a 14‐3‐3 isoform involved in aphid resistance. Issue 3 (24th October 2018) - Chaudhary, Ritu; Peng, Hsuan‐Chieh; He, Jiangman; MacWilliams, Jacob; Teixeira, Marcella; Tsuchiya, Tokuji; Chesnais, Quentin; Mudgett, Mary Beth; Kaloshian, Isgouhi
Summary: We demonstrated previously that expression of Macrosiphum euphorbiae salivary protein Me10 enhanced aphid reproduction on its host tomato ( Solanum lycopersicum ). However, the mechanism of action of Me10 remained elusive. To confirm the secretion of Me10 by the aphid into plant tissues, we produced Me10 polyclonal antibodies. To identify the plant targets of Me10, we developed a tomato immune induced complementary DNA yeast two‐hybrid library and screened it with Me10 as bait. Immunoprecipitation and bimolecular fluorescence complementation (BiFC) assays were performed to validate one of the interactions in planta, and virus‐induced gene silencing was used for functional characterization in tomato. We demonstrated that Me10 is secreted into the plant tissues and interacts with tomato 14‐3‐3 isoform 7 (TFT7) in yeast. Immunoprecipitation assays confirmed that Me10 and its homologue in Aphis gossypii, Ag10k, interact with TFT7 in planta . Further, BiFC revealed that Me10 interaction with TFT7 occurs in the plant cell cytoplasm. While silencing of TFT7 in tomato leaves did not affect tomato susceptibility to M. euphorbiae, it enhanced longevity and fecundity of A. gossypii, the non‐host aphid. Our results suggest the model whereby TFT7 plays a role in aphid resistance in tomato and effectors of the Me10/Ag10k family interfere with TFT7 function during aphid infestation.